Modification of microelectrode arrays with high surface area dendritic platinum 3D structures: Enhanced sensitivity for oxygen detection in ionic liquids - Hussain, G.; O mullane, A.; Silvester, Debbie (2018)
Electrochemical gas sensors are often used for identifying and quantifying redox-active analyte gases in the atmosphere. However, for amperometric sensors, the current signal is usually dependent on the electroactive surface area, which can become small when using microelectrodes and miniaturized devices. Microarray thin-film electrodes (MATFEs) are commercially available, low-cost devices that give enhanced current densities compared to mm-sized electrodes, but still give low current responses (e.g., less than one nanoamp), when detecting low concentrations of gases. To overcome this, we have modified the surface of the MATFEs by depositing platinum into the recessed holes to create arrays of 3D structures with high surface areas. Dendritic structures have been formed using an additive, lead acetate (Pb(OAc)2) into the plating solution. One-step and two-step depositions were explored, with a total deposition time of 300 s or 420 s. The modified MATFEs were then studied for their behavior towards oxygen reduction in the room temperature ionic liquid (RTIL) [N8,2,2,2][NTf2]. Significantly enhanced currents for oxygen were observed, ranging from 9 to 16 times the current of the unmodified MATFE. The highest sensitivity was obtained using a two-step deposition with a total time of 420 s, and both steps containing Pb(OAc)2. This work shows that commercially-available microelectrodes can be favorably modified to give significantly enhanced analytical performances.